Issues emerging in human musculoskeletal system simulation with mechanical and electromechanical rod structures - A. O. Blinov; A. V. Borisov; L. V. Konchina; M. G. Kulikova; K. S. Maslova (Известия высших учебных заведений: Проблемы энергетики)
Based on the statistical analysis of publications and patents located in the RSCI database for the keywords «exoskeleton», «anthropomorphic robot», «bionic prosthesis», interest in the research topic has been established, expressed in a significant increase in publications in recent years. It was revealed that most of the models use absolutely solid links in the form of rods.GOAL. Identification and study of problems arising in the modeling of anthropomorphic robotic systems. METHODS. Methods of mathematical modeling, analysis, comparison with a biological prototype, robotics, theoretical mechanics, electromechanics were used. RESULTS. The problem of accuracy of modeling by rod robotic systems with absolutely rigid links, a link of the human musculoskeletal system, is considered. The relative error of the accuracy of approximation by rods of a human limb is calculated, a conclusion is made about a significant error in the modeling of links. The problem of evaluating the influence of a rotating rotor of an electric motor on a mechanism model is considered. Next, the model is considered taking into account the rotating rotor and gearbox. It has been established that when modeling anthropomorphic mechanisms with rods, the problem arises of the need to take into account the dynamics of drives. An electromechanical model of a link with a DC motor is proposed. A significant increase in energy costs during the movement of the link has been established, in comparison with the model of an ideal hinge, in which the required control moment is created, which is a problem. A partial solution of the identified problems is proposed using the model of a variable length link containing three sections. CONCLUSION. The study made it possible to identify problems that arise when modeling the human musculoskeletal system with rod robotic electromechanical systems with absolutely solid links.